"We Have to Advocate so Hard for Ourselves and Our People": Caring for a Trans or Non-Binary Older Adult with Dementia. Issue 3 (27th May 2023) - Silverman, Marjorie; Baril, Alexandre
Abstract: This article reports on empirical findings from a Canadian study examining the experiences of carers who support a trans or non-binary person with dementia. Using a trans-affirmative, critical disability, anti-ageist, and intersectional approach, these findings fill an important gap in the literature. The narrative interviews with four participants reveal that there are unique features to caring for a trans or non-binary person with dementia, namely, becoming a carer due to marginalized status, performing care tasks linked to gender identity and expression, and managing multiple and specific forms of discrimination. Three of the four carers were themselves trans or non-binary, pointing to pathways into care that are linked to a shared marginalized identity. In addition to the traditional tasks of dementia care, the participants engaged in gender-related tasks such as gendered body care, sustaining the gendered self, and advocacy and future planning linked to gender identity and expression. The carers also had to manage numerous forms of cisgenderist, ageist, and cogniticist discrimination and violence directed at both the trans or non-binary person with dementia and themselves. This discrimination dramatically reduced care options, placing more responsibility on the shoulders of carers. The article ends with practical recommendations.